The role of major allergens Art v 1 and Art v 3 in Artemisia pollen-induced asthma: a mouse model study - Akhtemova, Nazugum; Sergazina, Akbota; Bolatbekov, Turlan; Rakhmatullayeva, Guliza; Tailakova, Elmira; Tabynov, Kairat; Fomin, Gleb; Zhao, Lan; Gao, Zhongshan; Tabynov, Kaissar (Frontiers in Immunology, 2025)
BackgroundArtemisia pollen is a major airborne allergen contributing to seasonal allergic rhinitis and bronchial asthma worldwide. However, the specific allergenic potential of different Artemisia species and their major allergens, Art v 1 and Art v 3, remains poorly understood.MethodsThis study utilized a BALB/c mouse model to comparatively assess the allergenic potential of A. vulgaris, A. absinthium, and A. annua. Mice were sensitized and challenged with standardized pollen extracts, and allergic responses were evaluated through serum IgE levels, airway hyperreactivity, ear swelling, and histopathological lung analysis. The correlation between allergen content (Art v 1 and Art v 3) and allergic outcomes was also examined.ResultsA. vulgaris exhibited the highest allergenicity, inducing the most pronounced IgE response, airway hyperresponsiveness, and severe pulmonary pathology. A. absinthium displayed intermediate allergenic potential, while A. annua elicited the mildest allergic response. Art v 1 levels strongly correlated with key clinical and pathological markers of asthma, whereas Art v 3 showed no significant association. Notably, the Art v 1/Art v 3 ratio emerged as the strongest predictor of pulmonary pathology.ConclusionThese findings establish Art v 1 as the key driver of Artemisia-induced allergic inflammation and emphasize its dominance over Art v 3 in pollen as a critical factor in the development of allergic lung pathology. These findings provide new insights into the molecular basis of Artemisia pollen allergy and may inform future diagnostic and therapeutic strategies.